An association of cocoa consumption with improved physical fitness and decreased muscle damage and oxidative stress in athletes - González-Garrido, J. A.; Garcia-Sánchez, J. R.; Garrido-Llanos, S.; Olivares-Corichi, I. M. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Several studies have demonstrated the protective effects of cocoa consumption, due to its anti-inflammatory and antioxidant properties. Acute exercise induces oxidative stress and causes muscular damage during training. This study was designed to examine the effect of cocoa consumption on the markers of muscle damage, oxidative stress and physical fitness in professional soccer players.